Analysis of Infection Prevention and Control Program Implementation on Nurses in the Room Dr. Fauziah Bireuen Hospitals Makasaar - Amirullah Amirullah; Asriwati Asriwati; Mappeaty Nyorong; Nur'aini Nur'aini; Endang Maryanti (PSPP JOURNALS, 2022)
The study aims to analyze the implementation of infection prevention and control programs. This type of research is qualitative with a phenomenological approach. The research informants were 11 people consisting of 3 nurses, 3 heads of rooms, 1 head of the PPI committee, 1 IPCN, 1 Deputy Director of Services, 1 Head of Nursing and 1 Head of Medical Services. The research was conducted in November–December 2021 through interviews and observations. The data were analyzed using qualitative descriptive through the stages of data reduction, presentation and conclusion drawing. It can be concluded that the implementation of the PPI (Infection Prevention Program) program is not entirely in accordance with SPO (Standard Operating Procedures) due to the lack of compliance by nurses, lack of implementation of aseptic actions in HAIs (Healthcare Associated Infection) bundles, lack of regular and inaccurate training. submission of monthly reports. So it is recommended for hospital management and staff to make policies that regulate the commitment of all health workers in implementing the PPI (Infection Prevention Program) program, being a role model / role model in the implementation of the PPI (Infection Prevention Program) program such as in inviting, familiarizing hand hygiene activities. , use of PPE (Personal Protective Equipment) and aseptic measures and routinely carry out training / training on a regular basis.